The conflict between love and interest for an ethic of extension (Mayéutica Revista Científica de Humanidades y Artes, 2026)
We reflect on the possibility of an ethical theory of extension, proposed by Francisco Varela and other authors. In particular, consider the role that love can play in theory and its complex relationship with the notion of interest. In Section I, we establish the proposal for ethical extension according to George Mead and Varela, who draws inspiration from Mencius. In Part II, we present Harry Frankfurt's analysis of love and the difficulties it brings. In section III, we review Adam Smith and Aristotle's concept of interest and its connection to love. In Chapter IV, we consider Ferdinand Tönnies' dualism as a critique of the possibility of extension, assuming an insurmountable conflict between love and interest. In Section V, we reviewed Émile Durkheim's response to Tönnies. We conluded that love and interest must play a role in a theory of ethical extension.
Keywords: Ethical extension; love; interest